2012
DOI: 10.1007/s13187-012-0362-z
|View full text |Cite
|
Sign up to set email alerts
|

An ET-CURE Pilot Project Supporting Undergraduate Training in Cancer Research, Emerging Technology, and Health Disparities

Abstract: The National Cancer Institute’s Center to Reduce Cancer Health Disparities has created pilot training opportunities under the “Continuing Umbrella of Research Experiences” (CURE) program that focus on emerging technologies (ET). In this pilot project, an eighteen month cancer biology research internship was reinforced with: instruction in an emerging technology (proteomics), a transition from the undergraduate laboratory to a research setting, education in cancer health disparities, and community outreach acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Faculty time is often divided into these separate areas, but there are advantages to facilitating overlap among them. Research has shown that engaging students in undergraduate research projects positively benefits a faculty member's own research and teaching goals (Elgren and Hensel, 2006;Potter et al, 2009;Wilson et al, 2012;Adedokun et al, 2013). Although mentoring undergraduate researchers benefits both faculty and students, it also presents substantial challenges (Bullough and Draper, 2004;Dolan and Johnson, 2010;Marquis et al, 2017).…”
Section: Faculty As Mentorsmentioning
confidence: 99%
“…Faculty time is often divided into these separate areas, but there are advantages to facilitating overlap among them. Research has shown that engaging students in undergraduate research projects positively benefits a faculty member's own research and teaching goals (Elgren and Hensel, 2006;Potter et al, 2009;Wilson et al, 2012;Adedokun et al, 2013). Although mentoring undergraduate researchers benefits both faculty and students, it also presents substantial challenges (Bullough and Draper, 2004;Dolan and Johnson, 2010;Marquis et al, 2017).…”
Section: Faculty As Mentorsmentioning
confidence: 99%
“…Many medical schools and healthcare institutions are implementing curricula in cultural competence and community engagement. 6,7 However, there are only a few programs offering research training for addressing disparities, and those that exist tend to focus on a single clinical area, such as cardiovascular disease 8 , cancer 9,10 , or methodology (e.g., community-based participatory research) 11,12 . Although we suspect that not all efforts are published, it appears that there is limited framework and data supporting the feasibility and impact of a general disparities research curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, a mix of both educational and research aspects were prominent in the most successful research programs. [3][4][5][6] Programs that focused on having an open-minded culture with interdisciplinary research facilities seemed to spark sustaining and meaningful collaborations. 7,8 Programs that sustained a feeling of social cohesion among undergraduate researchers (e.g.…”
Section: Introductionmentioning
confidence: 99%